PENGARUH PEMBERIAN KOMPENSASI, MOTIVASI KERJA DAN TERHADAP PENINGKATAN PRESTASI KERJA KARYAWAN - Taufik Rahmad Saleh; Muninghar Muninghar; Fatimah Riswati (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
This research was conducted St Bank Jatim, Sumenep Branch, with a total sample of 57 people. The purpose of this study are: 1) To find out how the description of compensation assistance, work motivation, and work performance at Bank Jatim, Sumenep branch; 2) To support and analyze participation in the provision of compensation and work motivation on employee work performance at Bank Jatim, Sumenep branch; 3) To support and analyze compensation complaints, work motivation and organizational work simultaneously on the work performance of employees at Bank Jatim, Sumenep branch. Data analysis using SPSS, this type of research is explanatory research using quantitative research. The results showed that: 1) Compensation (X1) at Bank Jatim, Sumenep Branch can be expressed according to employee expectations, namely the existence of all kinds of rewards in the form of money such as salaries, various benefits, THR, incentives, commissions and others. Motivation (X2) of employees at Bank Jatim, Sumenep Branch, have had such a strong drive, desire or interest in them to achieve organizational goals. This system of shared meaning already has a number of key characteristics that the Sumenep Branch of the Bank Jatim organization is upholding; 2) Simultaneously, Compensation and Motivation have a significant influence on Employee Performance at Bank Jatim, Sumenep Branch.